2004
DOI: 10.1097/00004872-200406002-01031
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Is Associated With Arterial Stiffness in Apparently Healthy Individuals

Abstract: Objective-C-reactive protein (CRP) levels predict outcome in healthy individuals and patients with atherosclerosis.Arterial stiffness also independently predicts all-cause and cardiovascular mortality and may be involved in the process of atherosclerosis. The aim of this study was to investigate the relationship between stiffness and inflammation in a cohort of healthy individuals. Methods and Results-Pulse wave velocity (PWV) and blood pressure were assessed in 427 individuals. Subjects with cardiovascular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1
15

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 6 publications
4
70
1
15
Order By: Relevance
“…32 Most studies have reported an association between arterial stiffness measured by AIx 33,34 and high levels of markers of inflammation including hs-CRP, although some only found hs-CRP to be associated with PWV. 35 Current smoking was associated with at higher AIx in young women compared with young men and also with a faster attenuation of this relationship with increasing age in women compared with men. Smoking has rather consistently been associated with increased AIx.…”
Section: Discussionmentioning
confidence: 88%
“…32 Most studies have reported an association between arterial stiffness measured by AIx 33,34 and high levels of markers of inflammation including hs-CRP, although some only found hs-CRP to be associated with PWV. 35 Current smoking was associated with at higher AIx in young women compared with young men and also with a faster attenuation of this relationship with increasing age in women compared with men. Smoking has rather consistently been associated with increased AIx.…”
Section: Discussionmentioning
confidence: 88%
“…10 -26 On aggregate, previous studies have shown higher CRP levels to be associated with greater arterial stiffness of elastic, 10 -14,16 -23 muscular, 25 or both types of arteries 26 and higher interleukin 6 levels to be associated with greater elastic arterial stiffness. 11,15 Taken together, these studies 10 -23,25,26 and the present results support the concept that low-grade inflammation may affect arterial stiffness.…”
Section: Discussionmentioning
confidence: 95%
“…Other potential mechanisms include the possibility that increased arterial stiffness predisposes to neurohormonal activation (25) or a generalized cardiovascular inflammatory response (26), which, in turn may contribute to the development of AF (27). The study illustrates the importance of considering target organ damage at the sub-clinical stage in the hypertensive patient and reopens the question of a potential benefit of anti-hypertensive agents beyond reduction in arterial blood pressure (28).…”
Section: Pwvmentioning
confidence: 89%